2013
DOI: 10.1002/cncr.28238
|View full text |Cite
|
Sign up to set email alerts
|

Use of prostate‐specific antigen testing as a disease surveillance tool following radical prostatectomy

Abstract: Background Prostate-specific antigen (PSA) testing is recommended every 6 to 12 months for the first 5 years following radical prostatectomy as a means to detect potential disease recurrence. Despite substantial research on factors affecting treatment decisions, recurrence, and mortality, little is known about whether men receive guideline-concordant surveillance testing or whether receipt varies by year of diagnosis, time since treatment, or other individual characteristics. Methods Surveillance testing fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
3
26
0
Order By: Relevance
“…Hispanic men actually had higher guideline concordance in this study than other populations, contrary to what has been demonstrated in the Medicare population. 10 Additionally, unmarried patients fare worse with respect to many health and prostate cancer-specific outcomes 31 including cancer surveillance in this study, suggesting that this population might also benefit from tailored interventions to ensure quality prostate cancer surveillance.…”
Section: Discussionmentioning
confidence: 81%
“…Hispanic men actually had higher guideline concordance in this study than other populations, contrary to what has been demonstrated in the Medicare population. 10 Additionally, unmarried patients fare worse with respect to many health and prostate cancer-specific outcomes 31 including cancer surveillance in this study, suggesting that this population might also benefit from tailored interventions to ensure quality prostate cancer surveillance.…”
Section: Discussionmentioning
confidence: 81%
“…Access to care was measured with at least one visit to a primary care provider during the baseline period (14). Receipt of active treatment was identified using inpatient, outpatient and carrier files with appropriate ICD-9 CM diagnostic and procedure codes, CPT or HCPCS codes or Revenue Center code during the six months after the index date (Appendix 1)(15, 16), (17). We classified the cancer treatment into four groups based on a hierarchy: 1) Radical Prostatectomy (RP); 2) Radiation Therapy (RT); 3) Hormone Therapy; and 4) None of the RP, RT or hormone therapy.…”
Section: Methodsmentioning
confidence: 99%
“…Trantham et al [10] reported that nearly 25% of African Americans did not have a PSA test for at least 12 months in the first 5 years after initial PCa. Non-Hispanic white men were more likely to receive at least one annual test during the first 5 years after PCa treatment than men of other ethnic groups based on SEER data.…”
Section: Diagnosismentioning
confidence: 99%